Multimodal Communication (De Gruyter Mouton, 2014)
Multimodal Communication is a venue for researchers in diverse fields of study, who explore varied & multimodal ways to conduct research & illustrate findings. It is open to papers from anthropology to art, math, psychology, science, & beyond. Articles share a commitment to developing multimodality and may use visuals/writing/sound to explore a theme; be highly theoretical or may be based on an empirical study integrating a number of modes.